2008 Sixth European Conference on Web Services 2008
DOI: 10.1109/ecows.2008.24
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Web Services in Mobile Networks

Abstract: Efficient solutions for Web services on mobile devices would allow truly global, platform independent, and interoperable information access, anywhere and at any time. While Web services are continuously gaining ground, they are commonly reserved for use on personal computers and high-capacity servers. However, mobile devices are gradually becoming more advanced in terms of processing resources and wireless communication capabilities, making it feasible to use Web services on such devices as well. Some of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In our previous work [12] we have shown that it is possible to utilize a mobile phone as a Web service client using SOAP, and that we can reduce the communication overhead by using compression. We used actual Universal Mobile Telecommunications System (UMTS) and General Packet Radio Service (GPRS) network connections.…”
Section: Requirementsmentioning
confidence: 99%
“…In our previous work [12] we have shown that it is possible to utilize a mobile phone as a Web service client using SOAP, and that we can reduce the communication overhead by using compression. We used actual Universal Mobile Telecommunications System (UMTS) and General Packet Radio Service (GPRS) network connections.…”
Section: Requirementsmentioning
confidence: 99%
“…Another standard for web services which is required to provide them with real-time capability and service quality control is discussed in [4] and WS-QoS Prediction is proposed to support other WS-QoS standards. XML compression is proposed for catering to limited bandwidth of military communications for web services [5], [7] & [13]. A comparison of standards for events notification for web services shows the developments in WSEventing and WS-Notifications Standards [6].…”
Section: Related Workmentioning
confidence: 99%
“…EXI was used in some of those researches [6,7] . For example, compression techniques [6] of Web service in mobile network is studied.…”
Section: Related Workmentioning
confidence: 99%
“…EXI was used in some of those researches [6,7] . For example, compression techniques [6] of Web service in mobile network is studied. Researchers in university of Finland aalto [7] analyzed different optimization methods such as HTTP compression, cache and agents in order to save energy consumption of mobile solutions.…”
Section: Related Workmentioning
confidence: 99%